Kesantunan Berbahasa dalam Berkomunikasi Masyarakat Watu Alo Kabupaten Manggarai - Stanislaus Hermaditoyo Stanislaus Hermaditoyo; Yohanes W. Dasor; Robert Hudin; Hilda Nia Engol (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
ABSTRACT Language politeness is a very important aspect of social life. By using polite language in every speech activity, it will have a positive impact on the participants of the speech. But in reality what happens in the community Manggarai Regency. The purpose of this study, namely (1) to describe the form of adherence to the principle of politeness in language communication in the Watu Alo community. (2) Describe the form of violation of the principle of linguistic politeness in interacting with the Watu Alo community. This type of research is qualitative using a qualitative descriptive method. The data collection method is the note-taking method. The listening technique means that the research's efforts to listen to the speeches of the Watu Alo people. Meanwhile, the note-taking technique means that the utterances of the Watu Alo community, both those who obey and violate the maxim of politeness in language the result showed that the language attitude of the Watu Alo people was polite. This can be seen from the analysis using five politeness scales, namely the profit and loss scale, the choice scale, the authority scale, the indirectness scale, and the social distance scale which are the benchmarks for whether an utterance can be said to be polite or not polite. Of the twenty data analyzed, the maxim of politeness in the language is the most frequently used, namely the maxim of wisdom namely two dates on obedience to the maxim of politeness, and the maxim of compatibility with three dates on compliance with the maxim of politeness. Of the six maxims of politeness in language, two maxims are often violated by both speakers and by speech partners, namely the maxim of appreciation and the maxim of compatibility. Keywords: politeness, speech, Watu Alo people.